KESEDERHANAAN VISUAL PADA MEDIA PEMBELAJARAN: ANALISIS TEORI BEBAN KOGNITIF UNTUK MENINGKATKAN FOKUS DAN PEMAHAMAN SISWA PAI - rozaqiy, robby; Abdul Aziz, Faqih; Naufal Abid, Muchammad; Abu Bakar, M. Yunus; Suryani (LPPM STAI Muhammadiyah Probolinggo, 2026)
The use of digital media in Islamic Religious Education (PAI) often falls into the trap of visually excessive design, which has the potential to fragment students' concentration. This article aims to examine the application of visual simplicity through the lens of Cognitive Load Theory to address issues of distraction and cognitive fatigue in students. This study employs a library research method with a qualitative approach. Data analysis draws from reputable journal literature using an interactive model encompassing data condensation, data presentation, and conclusion drawing. The findings indicate that visually dense media interfaces tend to increase extraneous cognitive load on students' working memory. Conversely, the reduction of irrelevant decorative elements suggests a potential decrease in such load, allowing working memory capacity to be more optimally allocated for core material processing (germane load). In conclusion, simplified media design is not merely an aesthetic choice, but a pedagogical strategy with the potential to enhance students' attention, sustain focus, and facilitate meaningful learning. Practically, this article contributes by offering a cognitive principle-based media design framework as a guide for PAI teachers in developing instructional media that is more mentally efficient and conducive to the internalization of moral values.